Cold seeps symphony - Losleben, Lisa Katrin; Clerici, Monica; Holm, Villads; Panieri, Giuliana (Septentrio Educational, 2023)
Focus:To listen to the Arctic Ocean’s sounds and to learn about the Arctic Ocean’s biodiversity, particularly near cold seeps. We will experiment with creating new sound expressions inspired by the Ocean. For pupils with hearing impairment, pupils can create a bodily expression of this and/or use instruments they are comfortable with.Learning objectives:With this activity pupils will start to understand:• The multitude of sounds audible in the Ocean and near to cold seeps at the sea-bed.• That the oceans, including the Arctic Ocean, harbors great biodiversity.• What an oceanographic ship is, and the anthropic sounds related to it.Key words:Ocean research, exploration, human/non-human relationship within ocean, sounds, place, noise.